Evaluating Government Consumption Expenditure Effect on Current Account in Nigeria: Array - Ugwu, Ephraim; Nwosa, P.I.; Ehinomen, C. (The Journal of Accounting and Management, 2021)
This study evaluates the interaction effect between government consumption expenditure and current account in Nigeria covering the periods from 1980 to 2019. The study answered the question, does government consumption expenditure affect the current account in Nigeria? Employing the Autoregressive Distributed Lag (ARDL) bound cointegration testing approach for evaluation, the unit root test results shows a mix order of stationarity. The ARDL bound test result show that there exists a long run relationship among the variables. The estimated coefficients of the long-run relationship are positive and statistically significant for the consumption expenditure, LOG (GCON), and the growth rate of GDP (GDPGR) at 5% significant level. This show that increased in the government consumption expenditure results to a decrease in the current account balance of Nigeria. The coefficient of budget deficit, DEFICIT shows a positive sign, indicating that government budget deficit leads to a current account deficit, thus supporting the twin deficit proposition. The study therefore recommend that the Federal Government of Nigeria should reduce the level of borrowing as this would reduce debt service payment.